DINAMIKA INVESTASI SYARIAH DALAM PASAR MODAL GLOBAL: KAJIAN AKUNTANSI DAN KEUANGAN - Irfa Febriyani; Rifatul Hanifah; Niken ning tiyas; Tahani Salsabila; A’aisyah Turrahmah; Agus Arwani (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research aims to provide a more comprehensive view of the development of the Islamic capital market. Through a deep understanding of these dynamics, strategic steps can be taken to overcome problems and take advantage of opportunities so that the Islamic capital market can continue to develop and make a positive contribution to the Islamic economy globally. The method used in this research is descriptive qualitative, namely by using a library research type approach. The type of data used in this research is secondary data. Islamic investment is a global phenomenon that continues to grow, but is still faced with a number of challenges that need to be overcome to build a stronger and more sustainable Islamic capital market. But it is still faced with challenges such as a lack of standardization, transparency, risk management and consistent regulations. Investors' confidence in the sharia market has a significant influence on their performance, with sharia investors tending to be more careful and conservative in investing. Sharia investment principles are different from conventional investments, with certain provisions that must be adhered to, such as the prohibition of usury, gharar and maysir. As well as facing the risk of gharar and jahalah as an essential component. This research provides an important contribution to the understanding of the dynamics of Islamic investments in global capital markets, which can be used by investors, regulators and other stakeholders to make more informed investment decisions. The implication is that it can increase the visibility of the sharia capital market; Synergy with global sustainable finance initiatives; Development of an inclusive and sustainable ecosystem; Challenges and opportunities; and The influence of advances in technology and knowledge.